Shakedown analysis of "soil-pile foundation-frame" system under seismic action = Przystosowanie układu "podłoże gruntowe pale-rama"? przy oddziaływaniach sejsmicznych - Alawdin, Piotr; Bulanov, George (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article, the seismic shakedown FEM analysis of reinforced concrete and composite spatial frame structures on the deformable foundation, taking into account the elastic-plastic and brittle behavior of structures elements, is presented. A foundation consists of group of the piles in the soil. The behavior of soil is described here using and the elastic half-space theory.
Keywords: seismic action; soil-structure interaction; frames; pile foundation; elastic-plastic elements; brittle elements; oddziaływanie sejsmiczne; podłoże odkształcalne; fundamenty; elementy sprężysto-plastyczne; elementy kruche